BREAKFAST QUALITY AS A POLICY ENTRY POINT TO PREVENT MALNUTRITION IN EARLY CHILDHOOD: KUALITAS SARAPAN SEBAGAI STRATEGI KEBIJAKAN UNTUK MENCEGAH MALNUTRISI PADA ANAK USIA DINI - Trisasmita, Laksmi; Nur Zakiyah Qhalby (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2025)
Malnutrition in early childhood remains a persistent challenge in Indonesia, particularly in rural communities. While existing interventions emphasize breastfeeding, complementary feeding, and main meals, the role of breakfast has been largely overlooked despite its potential contribution to preventing malnutrition. This study aimed to assess the relationship between breakfast quality and malnutrition among preschool children, as well as to identify policy gaps between actual practices and national nutrition standards. A cross-sectional study was conducted among 98 preschoolers aged 4–6 years in two rural kindergartens in Enrekang District, South Sulawesi. Nutritional status was determined using WHO BAZ, while breakfast quality was assessed using a locally adapted Breakfast Quality Index (BQI). Chi-square tests were applied for bivariate analysis, and logistic regression was used to determine protective factors. Policy gap analysis compared field data with national nutrition policies and the Free Nutritious Meal (MBG) program. The results showed that 69.4% of children had normal nutritional status, while 22.5% were undernourished and 8.1% overnourished, reflecting a double burden of malnutrition. Low-quality breakfast was significantly associated with malnutrition (p=0.018), and children with low-quality breakfasts were 4.2 times more likely to be malnourished than those with high-quality breakfasts (OR=4.20; 95% CI: 1.12–15.70). Policy gap analysis indicated that breakfast practices did not meet national standards, especially regarding dietary diversity, energy, protein, and micronutrient intake. These findings highlight breakfast quality as a potential policy entry point to address early childhood malnutrition through improved dietary diversity, parental awareness, school-based interventions, and local food utilization.